In vitro antiviral effect of sulfated pectin from Mangifera indica against the infection of the viral agent of childhood bronchiolitis (Respiratory Syncytial Virus - RSV) - Barboza, Mario Gabriel Lopes; Dyna, André Luiz; Lima, Thiago Ferreira; Tavares, Eliandro Reis; Yamada-Ogatta, Sueli Fumie; Deduch, Flávia; Orsato, Alexandre; Toledo, Karina Alves [UNESP]; Cunha, Arcelina Pacheco; Ricardo, Nágila Maria Pontes Silva; Galhardi, Ligia Carla Faccin (Elsevier, 2024)
The Human Respiratory Syncytial Virus (RSV) is the leading cause of acute respiratory infections in children. Currently, no safe, effective, or feasible option for pharmacological management of RSV exists. Hence, plant-derived natural compounds have been explored as promising antiviral agents. Mangifera indica is a globally distributed plant with reported anti-inflammatory, cardioprotective, and antiviral activities. Our study investigated the antiviral potential of a novel pectin from M. indica peels (PMi) and its chemically sulfated derivative (PSMi) against RSV in HEp-2 cells. The compounds were characterized using Fourier-transform infrared spectroscopy and nuclear magnetic resonance (NMR). NMR analysis revealed the presence of ester and carboxylic acid groups in PMi, and sulfation resulted in a sulfation degree of 0.5. PMi and PSMi showed no cytotoxic effects even at concentrations as high as 2000 μg/mL. PSMi completely inhibited RSV infectivity (100–1.56 μg/mL, 50 % inhibitory concentration of viral infectivity = 0.77 ± 0.11 μg/mL). The mechanism of action was investigated using the 50 % tissue culture infectious dose assay. PSMi displayed virucidal activity at concentrations from 100 to 6.25 μg/mL, and a significant reduction in viral infection was observed at all treatment times. Overall, PSMi is antiviral, cell-safe, and exhibits promising potential as an RSV treatment.
Keywords: Respiratory infection; Ribavirin; Sulfated polysaccharide